Laevifonol, Diptoindonesin A, dan Ampelopsin A, Tiga Dimer Stilbenoid dari Kulit Batang Shorea seminis V. Sl. (Dipterocarpaceae) - Nanik Siti Aminah; Sjamsul Arifin Achmad; Euis Holisotasn Hakim; Yana Maolana Syah; Lia Dewi Juliawaty; Emilia L. Ghisalberti (Jurnal Matematika & Sains, 2003)
Laevifonol (1), a dimer stilbenoid, namely a hybrid between Îµ-viniferin and ascorbic acid had been isolated from ethyl acetate extract of the stem bark of Shorea seminis V.Sl. The structure of this compound was determined on the basis of spectroscopic data.